Multidisciplinary management strategies for recurrent brain metastasis after prior radiotherapy: An overview - Kotecha, Rupesh; La Rosa, Alonso; Brown, Paul D.; Vogelbaum, Michael A.; Navarria, Pierina; Bodensohn, Raphael; Niyazi, Maximilian; Karschnia, Philipp; Minniti, Giuseppe (Neuro-Oncology, 2025)
As cancer patients with intracranial metastatic disease experience increasingly prolonged survival, the diagnosis and management of recurrent brain metastasis pose significant challenges in clinical practice. Prior to deciding upon a management strategy, it is necessary to ascertain whether patients have recurrent/progressive disease vs adverse radiation effect, classify the recurrence as local or distant in the brain, evaluate the extent of intracranial disease (size, number and location of lesions, and brain metastasis velocity), the status of extracranial disease, and enumerate the interval from the last intracranially directed intervention to disease recurrence. A spectrum of salvage local treatment options includes surgery (resection and laser interstitial thermal therapy [LITT]) with or without adjuvant radiotherapy in the forms of external beam radiotherapy, intraoperative radiotherapy, or brachytherapy. Nonoperative salvage local treatments also range from single fraction and fractionated stereotactic radiosurgery (SRS/FSRS) to whole brain radiation therapy (WBRT). Optimal integration of systemic therapies, preferably with central nervous system (CNS) activity, may also require reinterrogation of brain metastasis tissue to identify actionable molecular alterations specific to intracranial progressive disease. Ultimately, the selection of the appropriate management approach necessitates a sophisticated understanding of patient, tumor, and prior treatment-related factors and is often multimodal; hence, interdisciplinary evaluation for such patients is indispensable.
CRIS-Team Scopus Importer:2025-04-04
Keywords: brain metastases; progression; radiosurgery; radiotherapy; recurrence